Seal of Michael Opos, the Katepano of Iberia (1020s), from Taman - Victor Nikolaevich Chkhaidze (Античная древность и средние века)
So far, the excavations at the site of the ancient town of Taman (mediaeval Tamatarcha, or Matarcha) discovered a group of lead seals of the persons from 20 plus noble Byzantine families living in the eleventh and twelfth century. Among them there are the members of the Doukai, Komnenoi, Palaiologoi, Angeloi, Kastamonitai, Brachamioi, and others. Additionally, some of these seals uncover stable connections between eleventh-century Taman with the imperial themes, particularly in the Transcaucasia. This way, the previous finds of the seals at the ancient town of Taman include the pieces from the second quarter of the eleventh century, of Tornikios Barasbatze, the strategos of Kaloudia, and Theophylaktos Dalassenos. The new find presented in this article is a seal of Michael Opos, the katepano of Iberia. There is a parallel specimen originating from a private collection, but the title of protospatharios is not fully legible here. The chronology of this seal according to Michael’s title is no later than the 1020s. However, there still remain certain doubts about as to Michael’s, the owner of these seals, belonging to the Opoi, a family well-known in Byzantium. Although the well-known seal of Michael Opos from the Dumbarton Oaks collection shows Archangel Michael on the obverse, the two seals under present study feature St Demetrios of Thessalonike. These two seals write the family nickname as Ὠπάς (with alpha), though the seals of other family members show it with omega or omicron as: τῷ Ὠπῷ, τοῦ Ὠπου, τῷ Ὠπόν. This article also supplies information on 16 currently known rulers (katepanoi) of the theme of Iberia (1020s – 1072), supplying some amendments and variant chronologies.